2007
DOI: 10.1093/jn/137.9.2036
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Mitochondrial DNA Deletion, Content, and Biogenesis in Folate-Deficient Tissues of Young Rats Depend on Mitochondrial Folate and Oxidative DNA Injuries3

Abstract: We aimed to characterize folate-related changes in mitochondrial (mt) DNA of various tissues of young rats. Weaning Wistar rats were fed folate-deficient (FD) or folate-replete (control) diet for 2 or 4 wk. The mtDNA 4834-bp large deletion (mtDNA(4834) deletion) and mtDNA content were analyzed by quantitative real-time PCR. Compared with pooled 2-wk and 4-wk control groups, 4-wk folate deprivation significantly increased the frequency of the mtDNA(4834) deletion in pancreas, heart, brain, liver, and kidney and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
51
0
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(56 citation statements)
references
References 49 publications
3
51
0
2
Order By: Relevance
“…1). This finding is in accordance with our previous observation that an FD diet depleted brain folate levels and promoted the accumulation of large mtDNA deletions in whole-brain homogenates of rats (25) . A study has revealed that FD impaired mt antioxidant status, promoted superoxide overproduction and elevated mt protein oxidative damage (46) .…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…1). This finding is in accordance with our previous observation that an FD diet depleted brain folate levels and promoted the accumulation of large mtDNA deletions in whole-brain homogenates of rats (25) . A study has revealed that FD impaired mt antioxidant status, promoted superoxide overproduction and elevated mt protein oxidative damage (46) .…”
Section: Discussionsupporting
confidence: 93%
“…Consistently, we have previously shown that feeding rats an FD diet for 4 weeks elevated serum homocysteine levels, which were associated with brain oxidative DNA damage as well as increased hepatic lipid peroxidation (25,43) . Although elevated brain homocysteine levels were not measured in the present study, our data showed that 4 weeks of the FD diet significantly promoted higher levels of TBARS in the liver of rats, in parallel with FD-induced hippocampal folate depletion and oxidative lipid damage (Tables 2 and 3).…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Elevated levels of 8-OHdG have been associated with increased mtDNA deletions, mutation, and mtDNA loss (3,6,15,21). For instance, the levels of 8-OHdG and the mtDNA content were 50% higher and 75% lower, respectively, in the left ventricular tissue from end-stage heart failure patients compared with non-heart failure patients (22).…”
Section: Discussionmentioning
confidence: 99%
“…The quantiWcation of mtDNA 4834 deletion was determined by coamplifying the mtDNA displacement-loop (D-loop), mtDNA 4834 deletion, and nuclear-encoded -actin gene by real-time PCR (Chou et al 2007;Branda et al 2002). The Xuorescence spectra were monitored by LightCycler (Roche Diagnostics).…”
Section: Analysis Of Mtdna 4834 Deletion In LV Tissuesmentioning
confidence: 99%